Design ff an Octagonal Fractal Slot Loop Antenna Loaded With Dielectric Resonator and Optimization of its Parameters - Gupta, Sahil (My University, 2016)
Today's modern wireless communication system has transformed the universal telecommunication system into an integrated system as it is able to provide communication services to customer anywhere and anytime, whether in motion or fixed. Antenna is the very important constituent of the wireless communication system as it is responsible to radiate and receive the EM waves which are then converted into electrical signals for further processing. Performance of the antenna employed will affect the performance of the whole system. Today there is a great demand of devices which are smaller in size and capable of handling multiple frequencies for their operation, so compact size antennas with multiband behaviour and satisfactory gain are required. Fractal antennas are very much efficient in providing both the features hence; fractal geometry is applied on the designed antenna. Four concepts are used in the designing of the proposed antenna i.e. slot antenna, fractals, DGS (defected ground structure) and DRA (dielectric resonator antenna) to improve the radiation characteristics of antenna. Fractal slot loops are employed to increase the resonating bands and to decrease the fundamental frequency, Minkowski fractal geometry is applied on the boundaries of the octagonal shaped slot loop and iteration is carried up to second stage. CPW feed is used for excitation of antenna and stub matching technique is applied for the prevention of power loss. DGS is applied on the ground plane for reducing the size of antenna. A dielectric slab with high dielectric constant is placed on the designed prototype for increasing the bandwidth, increasing the gain and directivity of antenna. All the simulations are performed in CST (computer simulation technology) and simulated results are compared with the measured results. The antenna designed can operate at several wireless communication frequency ranges which can be used for GSM, Bluetooth, WLAN, WiMAX, IMT etc.
Master of Engineering-ECE
Keywords: Dielectric resonator Octagonal; DRA; Wi-MAX; Return Loss; DSG; Octagonal; Electronics and Communication